Complex ecological and socioeconomic impacts on medicinal plant diversity - Zhang, Ming-Xu; Chen, Yuan; Guo, Jing-Xia; Zhang, Ru; Bi, Ya-Qiong; Wei, Xin-Xin; Niu, Hui; Zhang, Chun-Hong; Li, Min-Hui (Frontiers in Pharmacology, 2022)
Medicinal plant diversity (MPD) is an important component of plant diversity, and field collection based on medicinal and economic value has the potential to damage the stability of the regional ecosystem. However, it is still unclear whether environmental and socioeconomic conditions have an impact on their distribution. Inner Mongolia accounts for 12.29% of China’s land area and 0.79% of the world’s land area and it has a long history of medicinal plant use. We used nine-years field survey of the distribution of medicinal plants in Inner Mongolia for assessing the distribution of MPD as influenced by environmental and socioeconomic activities by combining spatial analyses, species distribution models, and generalized additive models. The results from the spatial analysis show that the western region of Inner Mongolia is the main cold spot area of the MPD, and the central-eastern and northeastern regions of Inner Mongolia are the main hot spot areas of the MPD. Under the future climate change of shared socioeconomic pathways (SSP), areas with high habitat suitability for medicinal plants remain mainly dominated by the Yellow River, Yin Mountains, and Greater Khingan Range. Notably, the SSP245 development pathway remains the most significant concern in either long- or short-term development. The nonlinear relationship between the driving factors of MPD at different spatial scales shows that temperature, precipitation and socioeconomic development do have complex effects on MPD, which provides a reference for further studies on plant diversity and sustainable development and management. In this study, the spatial distribution of medicinal plant resources and the extent to which they are driven by ecological and socioeconomic factors were analyzed through a macroscopic approach. This provides a reference for larger-scale studies on the environmental and socioeconomic influences on the distribution of plant resources.